KInerja Keuangan dari Perspektif Keberlanjutan: Peran Kinerja Lingkungan, Modal Intelektual, dan Tata Kelola Perusahaan - Nur Aliyyah, Wandah; Vendy, Vicky (UMSurabaya Publishing, 2025)
This study examines the influence of environmental performance, intellectual capital, and corporate governance on the financial performance of energy sector companies listed on the Indonesia Stock Exchange during the 2021–2023 period. Secondary data were obtained from financial statements and PROPER rating reports. A total of 63 observations from 21 companies were selected using purposive sampling. Data analysis was conducted using panel data regression with the aid of STATA17 software. The results show that intellectual capital and the number of audit committee members have a positive and significant effect on financial performance. These findings indicate that efficient management of intangible assets and strong internal oversight mechanisms can enhance company profitability. Additionally, the proportion of independent commissioners exhibits a negative and significant effect on financial performance, suggesting potential ineffectiveness in oversight when not accompanied by sufficient engagement and competence.On the other hand, environmental performance, board size, and managerial ownership variables do not show significant effects. These findings imply that not all aspects of sustainability and corporate governance contribute directly to improvements in financial performance.